Alignment of Early Childhood Education and Elementary Teachers’ Perceptions of Inclusive Education During the Preschool–Primary Transition: A Mixed-Methods Study - Miki Ramayanti; Diana Diana; Deasylina Deasylina (AL-ISHLAH: Jurnal Pendidikan, 2026)
Inclusive education requires continuity across educational levels to ensure equitable learning opportunities for children with special needs (CWSN). However, alignment between early childhood education (PAUD) and primary school (SD) teachers during transitional periods remains underexplored, particularly in rural contexts where resource constraints are significant.This study employed a concurrent embedded mixed-methods design. Quantitative data were collected from 30 teachers (24 PAUD, 6 SD) using a structured Likert-scale questionnaire assessing knowledge, attitudes, and practices. Qualitative data were obtained through 12 interviews, 6 classroom observations, and document analysis. Descriptive and comparative analyses were conducted, alongside thematic analysis for qualitative data.Findings indicate that teacher perceptions of inclusive education are generally moderate and relatively similar across PAUD (M = 2.80) and SD (M = 2.85). While conceptual understanding is adequate, practical implementation remains limited. Alignment between teacher groups is evident at the attitudinal level but weak in classroom practices. Variations in training, teaching experience, and access to resources contribute to inconsistencies. Transition strategies are informal and unstructured, and parental and community involvement is minimal.The results highlight a gap between positive perceptions and effective inclusive practices, emphasizing the need for structured coordination mechanisms. Strengthening cross-level training, formal communication systems, and transition protocols is essential to improve alignment and ensure continuity of support for CWSN, particularly in rural educational settings.